When is R the union of an increasing family of null sets? - González Hernández, Juan; Hernández Hernández, Fernando; Villarreal, César Emilio (2007)
We study the problem in the title and show that it is equivalent to the fact that every set of reals is an increasing union of measurable sets. We also show the relationship of it with Sierpin’ski sets